Regulation of digital social networks, political propaganda and opposition discourse: A case study into the tension between Elon Musk and the Brazilian Judiciary - Fabbri Júnior, Duílio (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2025)
This article analyzes the political discourse surrounding the conflict between Elon Musk and the Brazilian Judiciary, particularly Minister Alexandre de Moraes, in the context of digital social network regulation. Its objective is to understand how polarized narratives are constructed and disseminated in a post-truth era marked by disinformation and ideological antagonism. Grounded in discourse analysis, the study justifies its relevance by the growing use of digital platforms for political influence and the absence of specific regulation in Brazil. The results reveal how both sides employ generalizations, emotional appeals, and ambiguity to legitimize their positions, turning social networks into arenas of political propaganda rather than democratic dialogue.